please solve this friends...
question no. 30
Attachments:
![](https://hi-static.z-dn.net/files/dc0/6b4cc7e01706906a25932be2189cf252.jpg)
Answers
Answered by
4
Answer:
tanθ = 1/2 (or) 1
Step-by-step explanation:
Given Equation is sin²θ - 3sinθcosθ + 1 = 0
⇒ 1 + sin²θ = 3sinθcosθ
Divide by 'cos²θ', we get
⇒ (1/cos²θ) + (sin²θ/cosθ) = (3sinθcosθ)/(cos²θ)
⇒ sec²θ + tan²θ = 3tanθ
⇒ (1 + tan²θ) + tan²θ = 3 tanθ
⇒ 1 + 2 tan²θ = 3 tanθ
⇒ 2 tan²θ - 3 tanθ + 1 = 0
⇒ 2 tan²θ - 2 tanθ - tanθ + 1 = 0
⇒ 2 tanθ(tanθ - 1) - (tanθ - 1) = 0
⇒ (2 tanθ - 1)(tanθ - 1) = 0
⇒ tan θ = 1/2 (or) 1
Hope it helps!
Answered by
1
Step-by-step explanation:
please mark me as brainliest
Attachments:
![](https://hi-static.z-dn.net/files/d58/e955581e49b038aa920161a36c186428.jpg)
Similar questions